2006
DOI: 10.1111/j.1365-246x.2006.03230.x
|View full text |Cite
|
Sign up to set email alerts
|

A correlation between theb-value and the fractal dimension from the aftershock sequence of the 1999 Chi-Chi, Taiwan, earthquake

Abstract: A correlation between the b-value and the fractal dimension from the aftershock sequence of the 1999 Chi-Chi, Taiwan, earthquake S U M M A R YWe analyse large number of aftershock events from the 1999 Chi-Chi, Taiwan, earthquake (M L 7.3) recorded around the epicentre area of the main shock in central Taiwan where events can be precisely located, due to dense coverage of modern seismometers. The seismicity is characterized by the b-value of the Gutenberg-Richter relation and the fractal (correlation) dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 28 publications
0
26
1
Order By: Relevance
“…5, he concluded that the b-value is not noticeably dependent upon fractal dimension. This result is different from the theoretical speculation by Aki (1981) and by Turcotte (1986a, b) and from observations (Hirata 1989;Wang and Lee 1996;Chen et al 2006). A possible reason for the difference might be that Wang (1991) considered a fractal distribution of the breaking strengths of the fault, while the others applied a fractal geometrical structure of the fault plane.…”
Section: Relation Of Frequency Versus Magnitude As Well As Energycontrasting
confidence: 56%
“…5, he concluded that the b-value is not noticeably dependent upon fractal dimension. This result is different from the theoretical speculation by Aki (1981) and by Turcotte (1986a, b) and from observations (Hirata 1989;Wang and Lee 1996;Chen et al 2006). A possible reason for the difference might be that Wang (1991) considered a fractal distribution of the breaking strengths of the fault, while the others applied a fractal geometrical structure of the fault plane.…”
Section: Relation Of Frequency Versus Magnitude As Well As Energycontrasting
confidence: 56%
“…A group of deeper aftershocks with two moderate events (M L = 6.3 and 6.0, respectively) exhibits a conjugate-fault system in the southern part of the source area, that is, a westward-dipping fault related to the two moderate aftershocks is conjugate to the eastward-dipping Chelungpu fault. Chen et al (2006) correlated the b-value to the fractal dimension (cf. Mandelbrot 1982;Lee 1996, 1997;Turcotte 1997), D, of hypocenters of aftershocks.…”
Section: The Chi-chi Earthquakes Of 20 September 1999mentioning
confidence: 99%
“…Nevertheless, they cannot rule out the possibility that the bursts originated from some non-seismic sources. Chen et al (2006) assumed that the bursts originated on the Chelungpu fault plane. This assumption makes the bursts unable be observable at this distance, assuming any reasonable value of crustal attenuation.…”
Section: The Pingtung Offshore Earthquake Doublets Of 26mentioning
confidence: 99%
See 2 more Smart Citations